Analyzing the Level, Predictors, and Institutional Readiness of Artificial Intelligence Awareness among Government Degree College Librarians in Visakhapatnam District - Dr. K. John Sudheer; Dr. M. Srinivasa Prasad (IJRDO - Journal of Social Science and Humanities Research, 2026)
Artificial Intelligence (AI) usage is turning into a constituent of academic libraries as it helps in the enhancement of information searching, automatization of cataloguing operations, digital referencing services, and data-driven decision-making. As more and more technology is used in learning institutions, librarians play a critical role in the application of AI tools in managing a library. However, the level of AI awareness, determinants of AI awareness, and the institutional readiness to embrace AI have not been effectively investigated particularly in government degree colleges within semi-urban and regional locations. The paper will analyze the level of AI awareness among the librarians in government degree colleges in the Visakhapatnam District, the primary predictors involved, and the desire of their institutions to adopt AI.The research will follow a quantitative model of the study through the use of a structured questionnaire, on a sample of librarians. The descriptive statistics were employed in determining the levels of awareness, and regression analysis was employed in identifying the significant predictors in this category of five which included professional training, ICT exposure, years of experience and institutional support. The dimensions were institutional readiness, including the presence of infrastructure, policy support, skills competence, and dedication to the leadership.The findings indicate that the level of AI awareness among librarians is moderate, and professional training and ICT competence are significant predictors of it. The institutional readiness was defined in the compartmentalized form with large flaws in the infrastructure and official policies on AI. The paper has highlighted the need to train systematically, train according to policy, and invest intentionally in digital infrastructure as potential remedies to the use of AI in scholarly libraries in Andhra Pradesh.